The Effect of PTSD Symptom Change on Suicidal Ideation in a Combined Military and Civilian Sample Engaged in Cognitive Processing Therapy. Issue 3 (May 2021) - Johnson, Clara M.; Holmes, Samantha C.; Suvak, Michael K.; Song, Jiyoung; Shields, Norman; Lane, Jeanine E.M.; Sijercic, Iris; Cohen, Zachary D.; Stirman, Shannon Wiltsey; Monson, Candice M.
Highlights: Suicidal ideation (SI) decreased during Cognitive Processing Therapy (CPT). Posttraumatic stress disorder (PTSD) symptoms predicted SI in the next CPT session. SI did not predict PTSD symptoms in the next CPT session. Gender and military status did not affect the relationship between PTSD and SI. Abstract: In light of the well-established relationship between posttraumatic stress disorder (PTSD) and suicidal ideation (SI), there has been a push for treatments that simultaneously improve symptoms of PTSD and decrease SI. Using data from a randomized controlled hybrid implementation-effectiveness trial, the current study investigated the effectiveness of Cognitive Processing Therapy (CPT; Resick, Monson, & Chard, 2016) on PTSD and SI. The patient sample ( N = 188) was diverse in military and veteran status, gender, and comorbidity, and 73% of the sample endorsed SI at one or more points during CPT. Participants demonstrated significant improvement in SI over the course of CPT. Multilevel growth curve modeling revealed a significant association between PTSD symptom change and change in SI. Results from cross-lagged multilevel regressions indicated that PTSD symptoms predicted SI in the next session, yet SI in a given session did not predict PTSD symptoms in the next session. Potentially relevant clinical factors (i.e., military status, gender, depression diagnosis, baseline SI, study consultation condition) were not associated with the relationship between PTSD symptoms and SI. These results add to the burgeoning literature suggesting that evidence-based treatments for PTSD, like CPT, reduce suicidality in a range of individuals with PTSD, and that this reduction is predicted by improvements in PTSD symptoms.